Magnificent delusions : Pakistan, the United States, and an epic history of misunderstanding - Ḥaqqānī, Ḥusain, 1956- (PublicAffairs, 2015)
"The relationship between America and Pakistan is based on mutual incomprehension and always has been. Pakistan--to American eyes--has gone from being a quirky irrelevance, to a stabilizing friend, to an essential military ally, to a seedbed of terror. America--to Pakistani eyes--has been a guarantee of security, a coldly distant scold, an enthusiastic military enabler, and is now a threat to national security and a source of humiliation."--Dust jacket.